Culture, Conflict, and Mediation in the Asian Pacific - Barnes, Bruce E. (Hamilton Books, 2007)
The countries of China, Taiwan, Singapore, Japan, Korea, Malaysia, Philippines, Indonesia, and Thailand are brought together for the first time in an integrated and systematic work outlining each country's cultural themes, cultural practices, and preferred conflict resolution mechanisms. The new "ADR" processes and centuries-old mediation and conciliation systems used in these countries are compared with the evolving mediation and ADR systems, including facilitation in North America and the West. This comprehensive study analyzes the cultural "themes" commonly found in these countries' religious conflicts; and presents over 30 different stories, case studies, and conflict resolution scenarios from the region. Culture, Conflict, and Mediation in the Asian Pacific looks beyond traditional regional boundaries to group Hawai'i with the nine Asian countries as an example of mediation systems and cultural influence on the most "Asian" of the U.S. states (over 2/3 of the population of Hawai'i is Asian-American).